A new species of the Craugastor podiciferus species group (Anura: Craugastoridae) from the premontane forest of southwestern Costa Rica - Arias, Erick; Chaveschaves, Gerardo; Crawford, Andrew J.; Parra-Olea, Gabriela (Zootaxa, 2016)
In this report, we describe a new species of the Craugastor podiciferus species group from the premontane forest of the Pacific versant along the Costa Rican-Panamanian border. Mitochondrial DNA and karyotype analyses previously showed a marked genetic divergence between populations of the premontane forest of the Fila Costeña and the lowlands South Pacific Costa Rica near Panama. Analyses of the mitochondrial DNA sequences and the morphological variation revealed significant differences between the populations of the premontane forest relative to the other populations of C. stejnegerianus, including the type locality. We recognize these premontane populations as a new species and show that they differ from the typical C. stejnegerianus in the coloration of the venter, the head and the body proportions, and mtDNA divergence. With the addition of this new species, the C. podiciferus species group now contains nine species.